Representasi Kekuasaan Perempuan Maskulinistik dalam Film Eternals - Verra Indah Irawati; Sunarto Sunarto (Interaksi Online, 2026)
This study analyzes the representation of masculine women's power in the film Eternals (2021) using Sara Mills' critical discourse approach and feminist theoretical frameworks, particularly the concepts of female masculinity and standpoint theory. Directed by Chloé Zhao, the film features four main female characters, Sersi, Ajak, Thena, and Makkari, who access powers conventionally coded as masculine within superhero narratives. The method employed is qualitative film text analysis, focusing on Mills' four levels of analysis: character, fragmentation, focalization, and schemata. The research findings demonstrate that masculine power in Eternals is not adopted directly without modification, but rather processed through negotiation with feminine concepts such as empathy, trauma, relationality, and care ethics. Sersi represents empathy-based leadership; Ajak demonstrates non-coercive spiritual power; Thena combines physical strength with psychological vulnerability; and Makkari presents inclusive female masculinity with disability representation. These representations indicate that women's power does not require sacrificing feminine identity to achieve legitimacy. The study concludes that Eternals does not merely depict women with masculine strength, but dismantles gender dichotomies by presenting power as a hybrid, fluid, contextual entity centered on women's experiences. This research provides a significant contribution to feminist discourse in popular cinema, particularly in critiquing and expanding understandings of power, heroism, and female agency within the superhero genre.